Homologs of Chemosensory Genes Have Roles in Behavior and Chemotaxis in the Root-Knot Nematode . - Shivakumara, Tagginahalli N; Dutta, Tushar K; Chaudhary, Sonam; Von Reuss, Stephan; Williamson, Valerie M; Rao, Uma (My University, 2019)
Nematode chemosensation is a vital component of their host-seeking behavior. The globally important phytonematode perceives and responds (via sensory organs such as amphids and phasmids) differentially to various chemical cues emanating from the rhizosphere during the course of host finding. However, compared with the free-living worm , the molecular intricacies behind the plant nematode chemotaxis are a yet-unexploited territory. In the present study, four putative chemosensory genes of , namely, , , , and were molecularly characterized. mRNA was found to be expressed in the cell bodies of amphidial neurons and phasmids of . , , , and transcripts were highly expressed in early life stages of , consistent with a role of these genes in host recognition. Functional characterization of , , , and via RNA interference revealed behavioral defects in and perturbed attraction to host roots in Pluronic gel medium. Knockdown of , , , and resulted in defective chemotaxis of to various volatile compounds (alcohol, ketone, aromatic compound, ester, thiazole, pyrazine), nonvolatiles of plant origin (carbohydrate, phytohormone, organic acid, amino acid, phenolic), and host root exudates in an agar-Pluronic gel-based assay plate. In addition, ascaroside-mediated signaling was impeded by downregulation of chemosensory genes. This new information that behavioral response in is modulated by specific olfactory genes can be extended to understand chemotaxis in other nematodes.
Keywords: nematode-plant interactions